Bangladesh : Inequalities in Utilization of Maternal Health Care Services, Evidence from MATLAB - Anwar, A.T.M. Iqbal; Killewo, Japhet; Chowdhury, Mahbub-E-Elahi K.; Dasgupta, Sushil Kanta (World Bank, Washington, DC, 2013)
This study investigates the equity implications of introducing a facility-based maternity care strategy in rural Bangladesh. The study took place in Matlab subdistrict in Chandpur District, where the Centre for Population and Health Research (ICDDR,B) had initiated a home-based maternity care program during 1987. During 1996-2001 the home-based strategy was replaced by a facility-based strategy that featured gradual upgrading of four ICDDR,B subcentres to provide basic emergency obstetrical care (EOC). During the 1997-2001 study period 19 percent of births took place in ICDDR,B facilities, 4 percent occurred in other facilities (public & private), and 2.6 percent births were attended by ICDDR,B midwives at home. The remaining deliveries took place at home without trained attendants. The study examines: 1) the extent to which poorer women in the community used the EOC services introduced and 2) the factors determining the use of those services. It does so by analyzing monitoring and service data from the ICDDR,B's maternity care program. The principal findings are that: (i) Women from poorer households used ICDDR, B delivery facilities significantly less than their better-off counterparts: the ratio between the best-off and worst-off 20 percent of the population was nearly 3:1. (ii) While overall facility utilization increased during the study period, the economic disparities in use persisted. (iii) Factors other than economic status associated with use of maternity care were area of residence, number of antenatal visits, birth order, maternal education and age, and year of delivery.